REKONSTRUKSI PARADIGMA MANAJEMEN MUTU TERPADU DALAM PENDIDIKAN ISLAM BERBASIS KEMANFAATAN HOLISTIK - Sarif Hidayatulloh; Sutrisno; Suwadi; Nadilla Aleyda Maqhfira Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study departs from the problem that Total Quality Management in education is often interpreted technocratically through administrative indicators, accreditation, and service satisfaction, whereas Islamic education requires quality that includes the formation of faith, knowledge, adab, morality, independence, and social benefit. This study aims to analyze the implementation of educational quality management, the manifestation of holistic benefit values, and the reconstruction of the Total Quality Management paradigm in Islamic education at Pondok Pesantren Tarbiyah Mubtadiin, which runs SMP NU Toboali in South Bangka. This research employed a qualitative case study design. Data were collected through in-depth interviews, observation, and documentation, and analyzed using thematic analysis followed by conceptual abstraction. The findings show that educational quality is implemented through participatory planning, the integration of formal schooling and pesantren education, discipline-based quality culture, multidimensional evaluation, and continuous improvement. Holistic benefit is reflected in the impact on students, families, society, alumni, and the institution. The reconstructed model consists of seven components: tawhidic and adab-based value orientation, integrative leadership, participatory planning, integrated curriculum, pesantren-based habituation, multidimensional evaluation, and sustainable socio-spiritual impact.